Study of chromium removal from wastewater using SSF-CW model: comparison between physical adsorption by coal CFA and phytoremediation by vetiver grass (Vetiveria Zizanioides L) - Titik Indrawati; Sarto Sarto; Agus Prasetya (Jurnal Rekayasa Proses, 2022)
The study aims to compare the effectiveness of chromium removal from water using adsorption by coal fly ash (CFA) and phytoremediation by vetiver grass (Vetiveria zizanioides L) as well as a combination of both CFA and vetiver grass. The experiment was carried out in four different reactors, having size of 100 cm (length) x 60 cm (wide) x 80 cm (height). One reactor was filled with gravel and CFA, without vetiver grass (RI), while another one was filled with gravel and vetiver grass, without CFA (RIV). The other two reactors were filled with gravel, CFA, and vetiver grass with the mass ratio of gravel/CFA of (25:2) and (25:1), denoted as RII and RIII, respectively. Fifty (50) L of synthetic wastewater containing 14.612 ppm of chromium was filled into the reactors and continuously recirculated for 15 days. Chromium accumulation in CFA and plants was analyzed on day 15. The results of plant development are indicated by the presence of new shoots and roots that grow during phytoremediation processes. In addition, there was an increase in weight and number of vetiver stems indicating the persistency of vetiver grass in such a harsh wastewater condition. The removal of Cr from wastewater in RI, RII, RIII and RIV at days 15 were 81%, 93.2%, 85.8% and 75.7%, respectively. It can be concluded that: (1) vetiver grass (Vetiveria zizanioides L) has high potential as phytoremediator plant, (2) Chromium adsorption by CFA plays important role in Cr removal from wastewater, and (3) combination of adsorption by CFA and a phytoremediation by vetiver grass significantly increases the removal of chromium from wastewater.